2013
DOI: 10.1371/journal.pone.0064220
|View full text |Cite
|
Sign up to set email alerts
|

Increased Leptin Response and Inhibition of Apoptosis in Thymocytes of Young Rats Offspring from Protein Deprived Dams during Lactation

Abstract: We investigated the consequences of mild maternal malnutrition in rat dams, in terms of thymocyte responses and the putative role of leptin. The young progeny of dams submitted to protein deprivation (PD) during lactation showed at 30 days of age lower body and thymus weights, significant alterations in CD4/CD8-defined T cell subsets without modifications in total thymocyte number as well as in proliferative response. Despite, the rats from PD group did not present alterations in leptin circulating levels, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 65 publications
1
17
1
Order By: Relevance
“…Interestingly, the anti-apoptotic gene Bcl -2 was upregulated by the protein restricted diet at 14 dpi. This is in accordance with other malnourishment models where BCL-2 protein was overexpressed in thymocytes of protein deprived mice, thereby protecting them from apoptotic stimuli30. In fact, Bcl -2 is a molecule induced by CXCR4 signalling31 and we observed here that increased expression of Bcl -2 correlates with increased expression of Cxcr4 .…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the anti-apoptotic gene Bcl -2 was upregulated by the protein restricted diet at 14 dpi. This is in accordance with other malnourishment models where BCL-2 protein was overexpressed in thymocytes of protein deprived mice, thereby protecting them from apoptotic stimuli30. In fact, Bcl -2 is a molecule induced by CXCR4 signalling31 and we observed here that increased expression of Bcl -2 correlates with increased expression of Cxcr4 .…”
Section: Discussionsupporting
confidence: 92%
“…75 The db/db mouse line, which lacks the leptin receptor, develops type 2 diabetes mellitus and obesity. In our own research, we have shown that db/db mice also undergo a precocious thymic involution, with severe loss of thymocytes and accumulation of adipocytes within the organ.…”
Section: Leptinmentioning
confidence: 99%
“…78 Accordingly, intrathymic leptin mRNA is selectively increased in microenvironmental cells in the young rats from protein-deprived dams, which in turn protects thymocytes from apoptosis. 75 The function of both leptin and ghrelin support thymopoiesis. In addition to changing the TCR repertoire, both hormones partially reverse age-associated thymic involution, albeit by distinct mechanisms.…”
Section: Leptinmentioning
confidence: 99%
“…Inhibitor of JB (IJB) retains NF-JB dimers in the cytoplasm, 12 and its degradation through IKK phosphorylation subsequently releases NF-JB dimers into the nucleus where they regulate the transcription of diverse genes, including cytokines, cell adhesion molecules, growth factors, and proapoptotic and antiapoptotic proteins. 12 Leptin binding to Ob-R is reported to inhibit cell apoptosis, 13 but its contributory role in the molecular mechanisms of cancer is yet to be elucidated.…”
mentioning
confidence: 99%